Improvement of Voltage Profile through the Optimal Placement of FACTS Using L-Index Method - K. Venkata Ramana Reddy; M. Padma Lalitha; PB Chennaiah (International Journal of Electrical and Computer Engineering (IJECE), 2014)
In this paper an IEEE standard test system is considered and it is tested using Newton-Raphson method with the help of MATLAB. The voltage magnitudes of each bus are examined and the corresponding weak bus is incorporated with FACTS such as SVC and TCSC. The optimal placement of FACTS can be identified using L-Index method. The value of L-index which approach unity implies that it reaches to instability. From this instability point the system stability is improved during steady state and Fault conditions. The disturbance is created in the system by changing the Load Reactive Power at a particular Bus.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5136